The Impact of the Hijab Fashion Trend on the Way of Dress and Moral Behavior of STEI Al-Furqon Prabumulih South Sumatra Female Students - Hanniyah; Siti Patimah; Meriyati (CV. Creative Tugu Pena, 2024)
The aim of this research is to find out how female STEI Al-Furqon Prabumulih students wear the hijab according to Islam. To find out how STEI Al-Furqon Prabumulih female students view the wearing of the hijab among STEI Al-Furqon Prabumulih female students. To find out the impact of the hijab fashion trend on the way of dressing and the Akhlakul Karimah behavior of STEI Al-Furqon Prabumulih female students. This research uses a qualitative approach. The results of these findings are that the way students dress at STEI Al-Furqon can be said to be in accordance with Islamic law, there are only a few people who still don't wear sharia clothing and they wear it when they are outside the campus, not inside the campus. How to wear the hijab, STEI Al-Furqon students also wear the hijab in accordance with Islamic law. Even though the hijab is not long, the hijab covers the chest and does not wear a thin hijab and also wears clothes that comply with Islamic law, supported by campus regulations.